Hybrid Auxetic Structures: Structural Optimization and Mechanical Characterization. Issue 5 (18th February 2021) - Bronder, Stefan; Adorna, Marcel; Fíla, Tomáš; Koudelka, Petr; Falta, Jan; Jiroušek, Ondřej; Jung, Anne
Abstract : With their increased energy absorption capacity, auxetic materials are perfectly fit to develop new, enhanced lightweight crash absorbers for cars. Herein, the mass distribution along the struts is optimized via finite element analysis with a parameterized optimization. Four different auxetic unit cells are taken from the literature and their struts parameterize, the models simulate, and the mass specific energy absorption capacity optimizes. The two models with the highest energy absorption capacity are then selected for experimental investigation and produced by additive manufacturing from a polymer. To further enhance the mechanical properties, the specimens are electrochemically coated with nickel and the polymer molten out by pyrolysis. Those Ni/polymer hybrids are subjected to quasistatic and dynamic impact experiments. Only a small strain rate sensitivity can be detected under dynamic loading, namely, a higher plastic collapse and higher plateau stress. The hollow struts are folding instead of bending, which render them much weaker than predicted by the simulation. In conclusion, it is possible to improve existing crash absorber elements with tailored auxetic hybrid structures. They absorb higher amounts of energy without changing their stiffness under dynamic loading while saving mass and cost. Abstract : Structurally optimized auxetic structures are superior to Ni/Al hybrid foams in terms of the energy absorption capacity. Although the coated Ni/polymer hybrid structures are brittle, the pyrolyzed hollow struts show a ductile failure. Under dynamic loading, the hollow strut structures show an increased energy absorption capacity compared with the quasistatic case while maintaining their stiffness.